First Language Transfer Found In The Students' Recount Text : A Study Of Indonesian Learners Learning English As A Foreign Language - Rohimah, Siti, Prof. Dr. Endang Fauziati, M. Hum, dra.Siti Zuhriah Ariatmi. M.Hum (2013)
This research is aimed at clarifying the types of language transfer, clarifying frequencies or dominants of language transfer and describing the sources of language transfer. In this study the writer uses Descriptive qualitative. The research was carried out at MTs N 1 Surakarta by taking 75 students from the grade two. The method of collecting data of this research is a test. The result of the research shows that students make errors in language transfer. The first language transfer in the students' recount text occurs on lexical level and syntactical level. Article is the highest level in lexical transfer; it reaches 15.78% with 18 mistakes and the lowest percentage is cognate. The highest grade of syntactical level is placed by word order; it reaches 81.25% with 13 errors and then the lowest is negation, it is only 1 error and reached percentage of 6.15%. The sources of the students' language transfer done by the students of MTs N 1 Surakarta are categorized into Selection Process, Interlanguage Identification, Blend and Autonomous Material, Structural Model, and Creating Equivalence. Some pedagogical implications concern to the teachers that have role as an agent of change in the education are Introducing of Contrastive Thinking Patterns in Class, Applying of suitable Learning Methodology in class, Introducing of Syntactical Transfer in Class, Introducing of Lexical Transfer in Class, and Classroom Management